Improving Procedure Text Writing Skills Through The Integration Of Picture Series Within Flipped Classroom Approach - Moh. Ainun Fitroni; Ulfatul Ma'rifah (Universitas Muhammadiyah Gresik, 2024)
The purpose of this study was to determine whether there was a significant effect of the picture series technique in writing procedure text in the eighth grade of MTs. M 06 Banyutengah. This study used a quasi experimental design consisting of one class as the treatment class and one class as the control class. The population in this study was the eighth grade of MTs. M 06 Banyutengah, and the samples of this study were students VIII A and VIII B Mts. M 06 Banyutengah school year 2023/2024. The sample was taken using purposive sampling. The instrument of this study was a writing test focusing on procedure text. The researcher collected data by giving a pre-test, giving treatment in the experimental class using the picture series technique with a flipped classroom, and finally giving a post-test. The data were analyzed with descriptive statistics and normality test. To test the hypothesis, the researcher used paired sample t-test, which was calculated through SPSS 25.0. The results of this study showed that the mean score the students' mean score raises in class experiment 23.66 points, from 43.00 (pre-test experiment class) to 66.66 (post-test experiment class), while the students' mean score raises in class control 16,83 points, from 42.83 (pre-test control class) to 59.66 (post-test control class). In addition, the Sig (2 tailed) value was 0.000. This means that the probability value (Sig) is lower than α (p-value < α or 0.000).